Macrophages enhance sodium channel expression in cardiomyocytes - Bogert, Nicolai; Therre, Markus; Din, Shabana; Furkel, Jennifer; Zhou, Xiao-Bo; El-Battrawy, Ibrahim; Heineke, Jörg; Schweizer, Patrick Alexander; Akın, Ibrahim; Katus, Hugo; Frey, Norbert; Leuschner, Florian; et al. (Basic research in cardiology, 2024)
Cardiac macrophages facilitate electrical conduction through the atrioventricular-node (AV) in mice. A possible role for cardiomyocyte-macrophage coupling on the effect of antiarrhythmic therapy has not been investigated yet. Holter monitoring was conducted in LysMCrexCsf1rLsL−DTR mice (MMDTR) under baseline conditions and after an elctrophysiological stress test by flecainide. In vivo effects were recapitulated in vitro by patch-clamp experiments. The underlying mechanism was characterized by expression and localization analysis of connexin43 (Cx43) and voltage-gated-sodium-channel-5 (Nav1.5). ECG monitoring in MMDTR mice did not show any significant conduction abnormalities but a significantly attenuated flecainide-induced extension of RR- and PP-intervals. Patch-clamp analysis revealed that the application of flecainide to neonatal rat ventricular cardiomyocytes (CMs) changed their resting-membrane-potential (RMP) to more negative potentials and decreased action-potential-duration (APD50). Coupling of macrophages to CMs significantly enhances the effects of flecainide, with a further reduction of the RMP and APD50, mediated by an upregulation of Cx43 and Nav1.5 surface expression. Macrophage depletion in mice does not correlate with cardiac electric conduction delay. Cardiac macrophages amplify the effects of flecainide on electrophysiological properties of cardiomyocytes in vivo and in vitro. Mechanistically, formation of macrophage-cardiomyocyte cell-cell-contacts via Cx43 facilitates the recruitment of Nav1.5 to the cell membrane increasing flecainide effects.
Online veröffentlicht: 09. Oktober 2024
Gesehen am 07.04.2025